The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1186/s12870-018-1489-9
|View full text |Cite
|
Sign up to set email alerts
|

Functional inactivation of OsGCNT induces enhanced disease resistance to Xanthomonas oryzae pv. oryzae in rice

Abstract: BackgroundSpotted-leaf mutants are important to reveal programmed cell death and defense-related pathways in rice. We previously characterized the phenotype performance of a rice spotted-leaf mutant spl21 and narrowed down the causal gene locus spl21(t) to an 87-kb region in chromosome 12 by map-based cloning.ResultWe showed that a single base substitution from A to G at position 836 in the coding sequence of Oryza sativa beta-1,6-N-acetylglucosaminyl transferase (OsGCNT), effectively mutating Tyr to Cys at po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Spotted-leaf mutants often show enhanced resistance to pathogen infection along with constitutive expression of defense response genes (Yin et al 2000; Mizobuchi et al 2002; Wu et al 2008; Xu et al 2018). In a rice spl21 mutant, upregulated expression of pathogenesis-related genes and increased level of jasmonic acid leads to enhanced resistance to bacterial blight pathogen Xanthomonas oryzae pv.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Spotted-leaf mutants often show enhanced resistance to pathogen infection along with constitutive expression of defense response genes (Yin et al 2000; Mizobuchi et al 2002; Wu et al 2008; Xu et al 2018). In a rice spl21 mutant, upregulated expression of pathogenesis-related genes and increased level of jasmonic acid leads to enhanced resistance to bacterial blight pathogen Xanthomonas oryzae pv.…”
Section: Discussionmentioning
confidence: 99%
“…In a rice spl21 mutant, upregulated expression of pathogenesis-related genes and increased level of jasmonic acid leads to enhanced resistance to bacterial blight pathogen Xanthomonas oryzae pv. oryzae (Xu et al 2018). In present study, spl40 mutant showed enhanced resistance to 14 races of this pathogen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the aforementioned mutants, the spl30 mutant also increased the resistance to rice blast ( Ruan et al, 2019 ), the cdr1 significantly increased rice blast resistance ( Takahashi et al, 2003 ), and the spl28 plants showed enhanced resistance to both blast and bacterial blight ( Qiao et al, 2010 ). Collectively, most of the rice LMMs show improved resistance to pathogens ( Xu et al, 2018 ; Tian et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lesion mimic mutants (LMMs) display spontaneous lesions in the absence of pathogen attack, environmental stress, or mechanical damage [1], exhibiting a similar phenotype to the pathogen infection-induced hypersensitive response (HR) mediated through programmed cell death (PCD) [2]. Programmed cell death plays an important role in the innate immunity of plants by initiating the cell death process to defend against pathogen infection [3]. In fact, most LMMs show increased resistance to pathogens: The spl30 mutant shows enhanced resistance to the bacterial pathogen Xanthomonas oryzae pv oryzae ( Xoo ); dj-lm shows enhanced resistance to rice blast ( M. oryzae ) [4]; and oscul3a shows enhanced resistance to both M. oryzae and Xoo [5,6].…”
Section: Introductionmentioning
confidence: 99%